Strategi Pengembangan Pariwisata Kreatif Berbasis Masyarakat (Community-based Creative Tourism) Di Bintan - Aditha Agung Prakoso; Yohana Aprilia de Lima (Journal of Tourism and Creativity, 2019)
The main focus of this research is to analyze and identify opportunities for developing community-based creative tourism in Bintan. Data analysis was performed by understanding and compiling both primary and secondary data that had been systematically collected. The results of the data analysis in this study were to create the concept of community-based creative tourism in Bintan based on its potential by developing creative zones based on seven creative sectors in Bintan with sustainable concepts and community empowerment to attract tourists, especially tourists from Singapore because the location of Bintan with Singapore is quite close and strategic. This is certainly an opportunity that must be utilized in terms of attracting foreign tourists visiting Singapore as well as foreign tourists from Singapore itself. It is also expected to increase the number of tourist visits to Indonesia, especially in Bintan.